On the fetection of dynamically screened scalar fields using atom interferometry - Stevenson, James (2017)
Dynamically screened scalar field theories form an attractive collection of models that were introduced to drive the late-time expansion of our universe. A common consequence of these theories is a screening mechanism which leads to the suppression of the fifth-forces mediated by the scalar field in sufficiently dense environments. This enables the models within this class of theories to avoid conflict with the stringent results from local tests of gravity, without the need for any fine tuning. The prototypical example of a dynamically screened scalar field is the chameleon model, for which screening arises due to the mass of the scalar responding to the local density. It has been recently demonstrated that atom interferometry is a powerful technique for constraining such scalars, with near future experiments capable of probing a large portion of the model parameter space. The nature of screening however means that closing in on what remains of the chameleon parameter space is going to become increasingly more difficult. This work aims to address this issue by examining the intricacies of how the chameleon field responds to the configuration of an atom interferometry experiment, where it is found that the non-linearities governing the theory can ultimately be harnessed in order to improve the prospects of detection.